Analysis of Primary Coating Thickness Effects on Adhesion Strength in S355J2+N Steel Material - Andika Adevicky Irwansyah; Muhammad Syukron; Atik Setyani; Muji Santoso (Journal of Metallurgical Engineering and Processing Technology, 2024)
Steel is a metal alloy primarily composed of iron, with carbon as its main alloying material along with several other components according to specific requirements. Low carbon steel has a carbon content of 0.05-0.3% and is easily manufacturable. This type of steel is commonly used for vehicle frames and other applications. The material used in this study is Carbon Steel S355J2, classified as low carbon steel with 0.15% carbon and 1.46% manganese. Carbon Steel S355J2 is used for the underframe of freight trains by PT Industri Kereta Api Indonesia. Coating and protection are crucial due to its susceptibility to corrosion, which can damage its structure in operational railway environments. As additional data for the company and learning for the researcher, a pull-off test was conducted varying the thickness of the primer coat. The results showed that sample A (110 µm), B (150 µm), and C (200 µm) achieved adhesion strengths of 2.5 MPa, 4.5 MPa, and 5 MPa respectively. The surface roughness level of the samples was 90 - 120 µm. Based on the test results, the most suitable coating system for the UGL underframe painting project for PT Industri Kereta Api (INKA) is a primer with a thickness of 150 µm (Sample B). This thickness is not too high, yet it significantly exceeds PT INKA's minimum criteria and avoids overcoating.